Improvement of the adhesion strength between copper plated layer and resin substrate using a chemically adsorbed monolayer - Tsuchiya K. (MATEC Web of Conferences, 2013)
With reducing the size and weight of electric devices, high-tensile, light and fine copper wire is demanded. So the production technique of a copper wire plated on a super fiber resin (Vectran film) was researched for improving the adhesion strength between the copper and the resin. In this study, we used the Cu2+ or Pd2+ complex prepared with a chemically adsorbed monolayer (CAM) to improve the adhesion strength between the copper plated layer and the Vectran film. As the result of scotch tape test, it was observed that the adhesion strength between the copper plated layer and Vectran film was improved by the Cu2+ or Pd2+ complex CAM.